We humans are the worst and the best and … - Rolston, Holmes, 1932-2025, author; Wiley Periodicals LLC, publisher (Colorado State University. Libraries, 2022)
We humans have extended culture amplifying our powers. Our genotypes are differentially expressed in phenotypes, increasing our preferring us over them, escalating our worst and best. Our groups are more ruthless than individuals. Our brain/minds are hyperimmense, neuroplastic in advancing our powers in collective technology. We fear reaching a tipping point, a point of no return, pending doom for humans and jeopardizing the planet forever. We humans are the best and the worst and … we have blundered into doubly compounded wickedness. We struggle to gain truth, and live with our biases, religious and secular. We are capable of the highest good, exemplified in individuals in their spiritual communities. We can also fall into enormous evil, made worse by our community allegiances. We are well into the greatest experiment ever, an Anthropocene Epoch in which the dangerous outcome cannot be undone, nor the experiment repeated.
Keywords: Anthropocene Epoch; artificial intelligence; communities; greater evil; greater good; human excellence; hyperimmense brain/minds; massacres; nations; neuroplasticity; one earth; religious; secular; truth; us versus them